Valorisation of Atlantic codfish (Gadus morhua) frames from the cure-salting industry as fish protein hydrolysates with in vitro bioactive properties. (September 2021) - Rodrigues, Daniela P.; Calado, Ricardo; Ameixa, Olga M.C.C.; Valcarcel, Jesus; Vázquez, José Antonio
Abstract: The fishing industry is often targeted as a producer of organic streams with low economic value. Biotechnological approaches can play a crucial role in transforming and adding value to these streams for their further use and upcycle. In this study, Atlantic codfish ( Gadus morhua ) frames, were subjected to Alcalase hydrolysis, whose optimal conditions were first fine-tuned and established as follows: 56.8 °C, pH 8.35, [Alcalase] = 0.25% ( v/w ) and 3 h of hydrolysis. Subsequently, under these conditions, a set of 5 L-pH-stat reactor validated the optimization tests. Our results showed that fish protein hydrolysates (FPH) exhibited a high yield of digestion (>80%) and a remarkable high degree of hydrolysis (37%). A high content of soluble protein (66 g/L), with an amino acid profile with viability for food and nutraceutical applications and a near total in vitro digestibility (>92%) were revealed. Moreover, antioxidant and antihypertensive activities were also detected. The hydrolysates presented an average molecular weight of 1709 Da and a peptide size distribution of 49% below 1 kDa and 41% in the range of 1–3 kDa. These findings suggest that Alcalase hydrolysis has the potential to recover functional bio compounds from codfish frames, boosting the economy through green technology. Highlights: Cod frame hydrolysates have hight protein content and relevant amino acid profile. Enzymatic hydrolysis allowed the production of peptides with low polydispersity. Cod frame hydrolysates have significant antihypertensive and antioxidant activity.